2016
DOI: 10.2217/bmm-2016-0148
|View full text |Cite
|
Sign up to set email alerts
|

Can Mean Platelet Volume and Red Blood Cell Distribution Width Show Disease Activity in Rheumatoid Arthritis?

Abstract: MPV and RDW were significantly higher in RA. RDW and MPV were similar to erythrocyte sedimentation rate and C-reactive protein to indicate inflammatory activity. RDW was correlated with pain and DAS28, but MPV was not associated with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…In addition, RDW is thought to be a marker for many pathological conditions (rheumatoid arthritis, inflammatory bowel disease, colon cancer, celiac disease, etc.) (26)(27)(28)(29). Chronic inflammation, aging, malnutrition, and anemia are thought to be underlying factors, but the pathophysiological basis of this relationship is uncertain (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RDW is thought to be a marker for many pathological conditions (rheumatoid arthritis, inflammatory bowel disease, colon cancer, celiac disease, etc.) (26)(27)(28)(29). Chronic inflammation, aging, malnutrition, and anemia are thought to be underlying factors, but the pathophysiological basis of this relationship is uncertain (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is routinely used in the differential diagnosis of anemia. Several studies in recent years have shown elevation of RDW in diseases such as coronary artery disease, cerebrovascular diseases, heart failure, diabetes-related complications, obstructive sleep apnea (OSA) syndrome, and rheumatoid arthritis [3,[5][6][7][8]. A study has even shown that high RDW is correlated with mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other previous study reported that PDW and MPV were not correlated with AS activity [21,22]. We assumed that the diverse confounding factors to affect PDW and MPV levels might result in these discrepancies [11][12][13][14][15][16][17][24][25][26]. With these reasons, in the present study, we excluded patients with AS who had abnormal laboratory results, and who had medical conditions such as hematologic diseases or history of medication administered affecting PDW and MPV such as antiplatelets [25,28] (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We consecutively screened and enrolled 141 patients with AS in this study, from March 2015 to October 2015, by the inclusion criteria as follows: (1) patients who fulfilled modified New York criteria for AS and who had been first diagnosed with AS at the Division of Rheumatology, Yonsei University College of Medicine, Severance Hospital [23]; (2) patients who had no medical conditions to affect PDW and MPV, such as abnormal glucose metabolism, chronic liver diseases, chronic kidney diseases, hypertension, dyslipidaemia, cardiovascular diseases, rheumatoid arthritis, and concurrent infection or hematologic disorders identified by 10th revised international classification of diseases [11][12][13][14][15][16][17]24,25]; (3) patients who had never received medications for diseases above searched by the Korean Drug Utilization Review system; (4) patients who had not received blocking agents against tumour necrosis factor (TNF), which are one of factors influencing the maturation of thrombopoietic cells and release of platelet into the circulation [26]. (5) Patients who had no concurrent infection and malignancy to enhance acute phase reactants levels; (6) patients who gave informed consent to their participation; (7) patients who took the assessment of disease activity indices of AS by independent physician on the same day of laboratory tests; (8) patients having laboratory results fulfilling the normal reference range as described in Figure 1 [27].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation